Artificial Intelligence (AI) in Support of Marketing - Panggabean, Helena Louise; Ryan Firdiansyah Suryawan; Indra Sani; Didin Sjarifudin (Dinasti Information and Technology, 2023)
The purpose of this paper can be more focused and informative to provide a better understanding of the concept of AI in the context of marketing, references derived from related literature. This paper uses qualitative methods by providing findings from various existing journal literature related to the topic, after that the findings are discussed and provide a view in the discussion in this paper. A search of the papers used in support of this paper dozens of articles related to the topic. The use of AI in supporting marketing strategies, such as increased efficiency, personalization, and campaign optimization. Describes how AI can be used to analyze consumer data at scale, including preferences, online behavior, and purchasing patterns. AI can help in identifying and solving marketing problems, as well as achieving business goals through in-depth data analysis and intelligent recommendations. challenges associated with implementing AI in marketing, including privacy concerns, data security, and ethical concerns. In addition, we also provide a second perspective, namely that this paper provides deep insight into how AI plays a supporting role in the marketing realm and its impact on business strategy and outcomes.Recommendations for the findings in this paper in addition to providing benefits and contributions to other researchers, can be developed into a follow-up research.